ICH and SDH post craniotomy evacuation and extraction of corpus alienum in traumatic brain injury - Akbar, Ilham; Setyono, Hanis; Ramadhana, Geizar Arsika; Jauhari, Muhammad Fauzan (Surgical Residency Program Syiah Kuala University, 2025)
Introduction: Traumatic brain injury (TBI) from trauma like gunshot wounds occurs when a sharp object penetrates the skull and brain tissue. Intracerebral Hemorrhage (ICH) and Subdural Hemorrhage (SDH) are common head trauma-related bleedings. ICH results from torn brain blood vessels, causing bleeding into brain tissue, while SDH occurs when bridging veins between the brain and dura mater rupture. Case description: A 4-year-old child presenting with decreased consciousness. Eight hours before admission, the patient was playing with his friend. While playing, the patient was hit by a gunshot wound to the head. After the incident, the patient complained of head pain that continued to worsen. On physical examination, there was tenderness and a subgaleal hematoma in the left parietal region. MSCT examination of the head without contrast was then performed on the patient. The patient underwent craniotomy to evacuate ICH, SDH, and extraction of bullet corpus alienum in the temporal region with C Arm guiding, with a total duration of 3 hours. The patient received treatment for 5 days after surgery. Conclusion: Intracranial pellet injuries from air gun shots can be fatal if they affect critical brain areas like the hypothalamus, thalamus, or brainstem. If accessible, prompt removal via craniotomy can improve outcomes by evacuating bleeding and relieving symptoms like headaches.